2011
DOI: 10.1590/s0102-33062011000200005
|View full text |Cite
|
Sign up to set email alerts
|

Limites térmicos para a germinação em função da origem de sementes de espécies de Eugenia (Myrtaceae) nativas do Brasil

Abstract: Limites térmicos para a germinação em função da origem de sementes de espécies de Eugenia (Myrtaceae) nativas do Brasil RESUMO (Limites térmicos para a germinação em função da origem de sementes de espécies de Eugenia (Myrtaceae) nativas do Brasil). A germinação das sementes é dependente de numerosos fatores abióticos, dentre os quais a temperatura fi gura entre os principais. No presente estudo analisou-se o comportamento germinativo de sementes de E. brasiliensis, E. involucrata, E. pyriformis e E. unifl ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
17

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 26 publications
(21 reference statements)
1
18
0
17
Order By: Relevance
“…The influence of temperature on the germination of the fruit seeds has been widely studied, and it is possible to know a little more about the characteristics of each species and the ability to grow or produce seedlings in certain places and seasons of the year. Experiments show and evidence the differentiated response according to the species, and Lamarca et al (2011) observed a wide adaptation to the emergence of seeds of some species of Eugenia in the most diverse temperatures tested, with germination and development of normal seedlings in the temperature range of 20 to 30ºC, being still indifferent to the temperature alternation (20/30 and 20/35ºC) and also reported by Lima et al (2007), who found higher rates for 'urucuzeiro' seeds at temperatures of 25, 30ºC and alternated between 20-30ºC. Silva et al (2006) observed better results for 'bacabinha' seeds when submitted to a temperature of 30ºC the same was verified by Oliveira et al (2005) for false annona muricata and by for 'jabuticabeira'.…”
Section: Sowing and Storage Testmentioning
confidence: 82%
“…The influence of temperature on the germination of the fruit seeds has been widely studied, and it is possible to know a little more about the characteristics of each species and the ability to grow or produce seedlings in certain places and seasons of the year. Experiments show and evidence the differentiated response according to the species, and Lamarca et al (2011) observed a wide adaptation to the emergence of seeds of some species of Eugenia in the most diverse temperatures tested, with germination and development of normal seedlings in the temperature range of 20 to 30ºC, being still indifferent to the temperature alternation (20/30 and 20/35ºC) and also reported by Lima et al (2007), who found higher rates for 'urucuzeiro' seeds at temperatures of 25, 30ºC and alternated between 20-30ºC. Silva et al (2006) observed better results for 'bacabinha' seeds when submitted to a temperature of 30ºC the same was verified by Oliveira et al (2005) for false annona muricata and by for 'jabuticabeira'.…”
Section: Sowing and Storage Testmentioning
confidence: 82%
“…A faixa térmica germinativa de 20 a 30 °C pode ser considerada adequada para as sementes de M. tinctoria, algo que parece se manter independente da origem do material, corroborando as faixas térmicas encontradas para diversas espécies florestais (Miranda & Ferraz 1999, Santos et al 2004, Mello & Barbedo 2007, Stockman et al 2007, Coelho et al 2008, Cardoso & Pereira 2009, Pires et al 2009, Pimenta et al 2010, Lamarca et al 2011.…”
Section: Resultsunclassified
“…à exigência luminosa, entre as procedências. Tais distinções podem ser reflexos da variabilidade genética das sementes ou das condições do ambiente de formação, uma vez que diversas características físicas e fisiológicas das sementes, como o teor de água inicial, os níveis de dormência e as exigências térmicas e fotoblásticas, podem ser influenciadas por variáveis meteorológicas, tais como temperatura, precipitação pluvial e fotoperíodo durante a formação das sementes (Laboriau 1983, Cardoso et al 1995, Daws et al 2004, Martins et al 2009, Lamarca et al 2011. Por outro lado, diversas características fisiológicas, principalmente o fotoblastismo, podem ter origem na herdabilidade genética das sementes, ou seja, seriam pouco sujeitas às variações do ambiente durante o desenvolvimento (Cardoso et al 1995).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Lamarca et al, 2011Lamarca et al, , 2013 report its use in tropical trees. Moreover, most the studies using thermal time as descriptor of plant development stages as influenced by temperature (Trentin et al, 2008) lack to validate the model by comparing the records with model predictions, i.e.…”
Section: Introductionmentioning
confidence: 99%